PUSAT HIBURAN DAN REKREASI KELUARGA INDOOR (FAMILY INDOOR THEME PARK) DENGAN PENDEKATAN ARSITEKTUR BIOKLIMATIK DI KOTA KENDARI - Siti Annisa Rahmadani Asri (GARIS Jurnal Mahasiswa Jurusan Arsitektur, 2022)
Entertainment and recreation is a very important need for human life as one of the 14 components of human needs. Theme parks as a place for family-oriented entertainment and recreation activities with indoor rides are indispensable in Kendari City. The design was carried out using data collection methods through unstructured interviews and literature studies as well as precedent studies. Then proceed with data analysis that produces the concept of design, design, and model. The results of the study concluded that the planning location is in Poasia District, in the trade and service area, recreation area and city green area. With the application of bioclimatic architecture in designing a building design, one must think about the application of building designs that adapt to the local environment or climate. Save energy by looking at the conditions around you and having a good impact on health. With certain design strategies, buildings can modify an uncomfortable outdoor climate into a comfortable space climate without consuming a lot of energy.